Ethics. contemporary perspectives : the ethics of ethics - Richards, Bernadette (ATF Theology, 2013)
The Ethics of Ethics Contributors: Jacques Arnould Ethics Adviser, CNES - Centre National d'études Spatiales, Paris. Robert Crotty University of South Australia, Adelaide. Grant Gillett University of Otago, Dunedin. Allan C Hutchinson Distinguished Research Professor Osgoode Hall Law School, York University, Toronto. Editor: Dr Bernadette Richards Law School University of Adelaide, Editor in Chief.